The Circular Economy of Herbal Beverage Products and Their Physicochemical Characteristics - Soesilowati, Etty; Susanti, Evi; Prihatini, Hikmah Tri (Society, 2023)
The circular economy seeks to maximize resource utility while enhancing waste materials’ added value. Herbal beverages are derived from biopharmaceutical plants, commonly using ginger, cardamom, turmeric, aromatic ginger or lesser galangal, and curcuma. This study had two primary objectives: (1) to analyze the physicochemical characteristics of instant ginger, instant turmeric, and instant ginger beverages, and (2) to enhance the economic value of production waste by converting it into liquid organic fertilizer (POC). The research was conducted at the small and medium enterprise “AIG Bunda Nisa” in Semarang Regency, Indonesia. Physicochemical characteristics were assessed through proximate analysis, and the quality of the POC was evaluated based on the standards set by the Indonesian Ministry of Agriculture (No.216/KPTS/SR.310/M/4/2019). The findings revealed that waste from the production of instant herbal drinks can be effectively repurposed as POC. The analysis showed that instant ginger beverages have higher ash and carbohydrate content than fresh ginger but lower total fat and protein content. Additionally, instant ginger beverages’ caloric value and carbohydrate content are higher than fresh ginger. Conversely, instant ginger’s protein content is lower than fresh ginger’s. In the case of turmeric, the ash, total fat, moisture, and protein content in fresh turmeric were lower than in instant turmeric beverages.